2012
DOI: 10.21236/ada564819
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Enhancing U.S. Army Company Grade Officer Career Continuance

Abstract: This report recommends potential initiatives to improve the retention of company grade officers. The report builds on prior work completed for the ARI research program entitled "Strategies to Enhance Retention" (STAY). The officer portion of the STAY program sought, over a three-year period, to improve the continuance of the Army's company grade officers. The recommendations are based on (a) focus groups and interviews on Army posts, (b) interviews with other subject matter experts, (c) literature review, (d) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is also a significant issue for the Army, because the strength of the Army's officer corps is determined in part by whether or not company grade officers remain in the Army and advance from company grade officers to field grade officers and beyond (Langkamer & Ervin, 2009). Officers in their first ADSO indicate that their intention to leave the Army is a result of a number of factors, including lack of work predictability, excessive operational pace, unmet career expectations, and perceptions that the Army is not committed to them or their families (Johnson, Hezlett, Mael, & Schneider, 2009). …”
Section: Statement Of the Problemmentioning
confidence: 99%
“…It is also a significant issue for the Army, because the strength of the Army's officer corps is determined in part by whether or not company grade officers remain in the Army and advance from company grade officers to field grade officers and beyond (Langkamer & Ervin, 2009). Officers in their first ADSO indicate that their intention to leave the Army is a result of a number of factors, including lack of work predictability, excessive operational pace, unmet career expectations, and perceptions that the Army is not committed to them or their families (Johnson, Hezlett, Mael, & Schneider, 2009). …”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Time 2 ratings were significantly higher for career satisfaction, satisfaction with leadership, job involvement, satisfaction with pay, perceived organizational support, work/family conflict, and career intentions. Many of these things were identified in our focus groups and interviews as factors that negatively influence retention decisions (Johnson, Hezlett, Mael, & Schneider, 2009), so it is not surprising that improved attitudes toward these factors coincides with more positive career intentions. Examination of attitude changes within brigades that participated in the evaluation study at different times indicated that there was likely not a single event or change in circumstances beyond our training intervention that influenced attitudes.…”
Section: Discussionmentioning
confidence: 86%
“…Career satisfaction and satisfaction with leadership improved following counseling training in every analysis we conducted. These were two of the factors that we identified as having the largest influence on retention decisions in our focus groups and interviews (Johnson et al, 2009). Attitudes that were not influenced in any of our analyses included Army identity salience, normative commitment, satisfaction with education/training opportunities, perceived economic constraint, support for family, family adjustment, spouse satisfaction, unit cohesion, and thoughts of leaving.…”
Section: Discussionmentioning
confidence: 90%
“…The work described here on enlisted retention was conducted in conjunction with a parallel effort that was directly focused on officer retention (Johnson, Hezlett, Mael, & Schneider, 2009). Wherever possible, we worked together with the officer project team, and many of the data collections and meetings described in this report were conducted jointly.…”
Section: The Enlisted Stay Projectmentioning
confidence: 99%